EFEKTIVITAS PENERIMAAN PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA SELAMA PANDEMI COVID-19 DI DESA SUAK PUNTONG - Maisarah, Siti; Ilhamsyah, Fadhil (Jurnal Ilmu Administrasi Negara (JUAN), 2022)
The purpose of writing this article is to review the effectiveness of data collection and distribution of Village Fund Cash Direct Assistance in terms of timing, effectiveness in determining the choice of distribution of Village Fund Cash Direct Assistance, and effectiveness in targeting the selection of the Suak Puntong village community who are entitled to receive direct cash assistance. Village Fund. The focus of the problem is seen from the decisions of the village apparatus in determining the selection of Candidates for the Village Fund Direct Cash Assistance, the period of receipt of the Village Fund Cash Direct Assistance, as well as the evaluation of the local community towards the people who receive this program. The method used in this research is a qualitative research method with a descriptive approach. Data collection was taken by interviewing, observing and documenting the local community and several village government officials. Other data used was in the form of a document for distributing BLT-Village Funds sourced from the Suak Puntong village office. The results of this study indicate that the distribution of BLT-Village Funds in terms of timeliness has not been fully declared effective, in terms of accuracy in determining choices and accuracy of targets, although errors occur at the beginning, they can be handled properly.